Tending the Field of Mindfulness-Based Programs: The Development of International Integrity Guidelines for Teachers and Teacher Training - Kenny, Maura (Glob Adv Health Med, 2020)
Since Jon Kabat-Zinn first introduced a contemporary, secularized application of mindfulness for the relief of pain and stress in physical health-care settings, there has been a significant and rapid expansion of the range of mindfulness-based programs (MBPs) designed for various health care, education, workplace, and other settings. As is common with developing programs, these often run ahead of carefully considered and researched effectiveness evaluations. This raises questions of how to best train mindfulness teachers to skillfully facilitate such interventions while minimizing the potential for harm. In this article, we describe the work of an international group of senior teacher trainers who met to develop guidelines on the ethics and standards for teacher trainers and their training pathways. In this article, we will define MBPs; describe the process by which these international guidelines were developed; and share details of the collaborative team who made up the international network that worked on them. We offer these guidelines as “living documents” that specifically set out: (1) ethical standards for mindfulness teachers and trainers; (2) criteria and standards for teacher trainers; and (3) criteria and standards for training pathways. As “living documents,” these will continue to be commented on and refined over time. Given that MBPs offered within secular settings in most countries currently have limited oversight or accreditation processes, we hope these guidelines will provide support and clarity to the teachers of all established and emerging MBPs, and their trainers and supervisors.